Aplikasi Reservasi Tempat dan Pemesanan Menu pada Restoran Central Cabang Kelapa Gading Berbasis Desktop dan Mobile - Adrian Hartanta (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Central Restaurant is a chinese food restaurant that has several branches one of them is in Kelapa Gading. Everyday Central restaurants are quite crowded by buyers. At  Central restaurant located in Kelapa Gading, ordering process still using conventional way, that is by writing customer order in paper. Therefore an application will created  for reservation place and ordering menu with desktop and mobile application and web service as a server for connecting desktop and mobile applications. For determine the most appropriate web service for desktop application, conducted testing for comparing two differents web service there are SOAP and REST web service. From the result of comparison testing speed web service REST has a speed sligthtly faster than SOAP web service. The testing for user level satisfaction with the showed that the level of user satisfaction on apalikasi quite satisfied.